Ramp-up planning for aircraft assembly production considering learning effect - Bao, Zhongkai; Chen, Lu (Computers & industrial engineering, 2025)
China’s commercial aircraft manufacturing is entering into the ramp-up phase during which the cycle time is accelerated. This paper studies the production ramp-up planning problem for an aircraft final assembly line considering learning effect. The decision is to determine the cycle time acceleration strategy, with the objective to guarantee the production efficiency of the assembly line in the ramp-up phase. A mixed-integer linear programming model that incorporates a Gauss-DeJong learning curve is developed to formulate the problem. Variable bounds and valid cuts are tailored to enhance the model. An exact solution approach based on a logic-based Benders decomposition algorithm is proposed to solve the problem. Comparative experiments reveal a significant improvement in computational performance of the proposed approach compared to the commercial solver. Managerial insights are discussed by addressing the real aircraft final assembly line. •Study the ramp-up planning problem for aircraft assembly considering learning effect.•A model is used to determine when and how much to adjust the production cycle time.•Some enhanced modeling strategies and a decomposition algorithm is proposed.•Algorithm performance and managerial insights are discussed by solving a real problem.